968. Leveraging On-Demand Digital Education to Increase ID Specialists' Knowledge and Confidence on Appropriate Probiotic Use for CDI Prevention. (4th December 2021) - Armagan, Allison; Hurst, Simi Thomas
Abstract: Background: Probiotics are increasingly being used in healthcare. As the number of probiotic options and their potential uses increase, it has become more challenging to make an informed selection for a given disease state. This study assessed the ability of digital education to improve Infectious Disease (ID) specialists' knowledge regarding the use of probiotics in preventing Clostridioides difficile infection (CDI) and antibiotic-associated diarrhea (AAD). Methods: A CME/ABIM MOC certified, educational program featuring a panel of 3 expert ID faculty was developed. The program sought to clarify the role of different probiotic strains in the prevention or treatment of different disease states. Educational effectiveness was assessed with a repeated-pairs pre-/post-assessment study design; each individual served as his/her own control. A chi-square test assessed changes pre- to post-assessment. P values < 0.05 are statistically significant. Effect sizes were evaluated using Cramer's V (< 0.05 modest; 0.06-0.15 noticeable effect; 0.16-0.26 considerable effect; > 0.26 extensive effect). The activity launched on a website dedicated to continuous professional development. Data for this matched-learner analysis were collected through 09/09/20. Results: To date, 7122 HCPs, including 5068 physicians, have participated in the activity. Data from the subset of ID specialists (n=235) who answered all pre-/post-assessment questions during the initial study period were analyzed. Following activity participation, significant improvements were observed in the proportion of ID specialists who answered assessment questions correctly (47% pre vs 69% post; P < .0001; V=.22). Improvements were also observed in several specific areas of assessment (Table) and confidence in their ability to select a probiotic-based on strain- and disease-specific efficacy (36% increase). Conclusion: Participation in this online educational program significantly improved ID specialists' understanding of the interplay between strain- and disease-specificity in the context of probiotics. These findings highlight the potential for well-designed online education to positively impact physicians' knowledge and confidence Disclosures: All Authors : No reported disclosures